Optimization of Eugenia punicifolia (Kunth) D. C. leaf extraction using a simplex centroid design focused on extracting phenolics with antioxidant and antiproliferative activities - Dos Santos, Catarina [UNESP]; Mizobucchi, Andressa Lie [UNESP]; Escaramboni, Bruna [UNESP]; Lopes, Bruno Pereira [UNESP]; Angolini, Celio Fernando Figueiredo; Eberlin, Marcos Nogueira; De Toledo, Karina Alves [UNESP]; Núñez, Eutimio Gustavo Fernández (Springer Nature, 2020)
Eugenia punicifolia (Kunth) D. C. (Myrtaceae) has been showing interesting biological activities in the literature which was correlated to its phenolic compounds. In the sense of a better recovering of phenolics with the best antioxidant and antiproliferative activities, an extraction, based on multivariate analytical approach, was developed from E. punicifolia leaves. The different extractor solvents (ethanol, methanol and water) and their binary and ternary combinations were evaluated using a simplex-centroid mixture design and surface response methodology. The optimized crude extracts were investigated for phenol and flavonoid content and compared to their antioxidant (EC50) and antiproliferative properties against HEp-2 (cell line derived from the oropharyngeal carcinoma) and mononuclear viability cells. Ethanolic extracts showed the best phenolic content with the highest antioxidant activity and moderated activity antiproliferative to HEp-2. ESI-QTOF-MS revealed the presence of quercetin and myricetin derivatives, which was correlated to activities tested. Then, simplex-centroid design allowed us to correlate the Eugenia punicifolia biological activities with the extracts obtained from solvent different polarity mixtures.[Figure not available: see fulltext.]
Keywords: Antioxidant; Antiproliferative activities; Eugenia punicifolia; Extraction; Mixture design